Química por meio de imagens: a fotografia com enfoque na Educação Ambiental como proposta de ensino e aprendizagem na EJA - PRESTES, Maria Aparecida Conceição Marconcini (2023)
This dissertation focuses on photographic art as a dynamic alternative in Natural Sciences and its Technologies, for critical Environmental Education, from a Freirean perspective, applied in Youth and Adult Education (EJA). The objective was to investigate the teaching-learning process of Chemistry, in schools in the Maranhão State Network, which offer EJA In-person – High School, in Imperatriz, on the use of photographs to articulate scientific knowledge problematized in social practice for Environmental Education critical, with a view to developing the Educational Research Product (PEP), materialized as a digital photobook for critical and ecological formation. It is an intervention research in Education, with a qualitative approach, having as collaborators 10 Chemistry teachers who worked at EJA, in 2022. We used semi-structured interviews to obtain data, which were analyzed using Discursive Textual Analysis (ATD), from the perspective of Moraes and Galiazzi (2016). The results were presented in three metatexts, structured/based on creative writing, based on emerging categories, through descriptive/discursive analyzes for interventions in the social discourses investigated: in Metatext 1, we outline an overview of the teaching-learning of Chemistry at EJA , the teaching methodologies and resources used, main difficulties and specificities of the subjects of the modality; in Metatext 2, we address the need for civic and ecological formation in EJA, as it contributes to the ethical-critical stances of its subjects, based on the teaching perceptions observed about Environmental Education (EE), with a predominance of naturalist, conservationist and anthropocentric conceptions; in Metatext 3, we highlight the importance of imagery resources in learning Chemistry and the possible skills, from a teaching perspective, that can be developed using photographs for critical Environmental Education. The digital photobook “Riacho Santa Teresa: an investigative/critical look at our streams, based on photographs”, with Problem Resolution Methodology, was produced for applicability in the EJA school context. The results obtained from this investigation can be configured as a contribution and extension for further research in Educational Intervention, within the field of Social Sciences, in the context of Adult and Youth Education (EJA) and critical Environmental Education in Natural Sciences and their Technologies. This includes considerations for contributions to improvements in the teaching-learning process of Chemistry, particularly through a proposed pedagogical intervention utilizing photographs for Problem Solving. The aim is to foster an interdisciplinary approach between Visual Arts (Photographs) and Natural Sciences (Chemistry), serving as a stimulus and motivation for other educators.